Peningkatan Kompetensi Manajemen K3 Konstruksi Sebagai Upaya Pencapaian Karakter Budaya Mutu Pada Siswa SMK - Diah Sarasanty; Nizar Zulfika, Dicki; Tri Asmorowati, Erna; Sholikhah, Faizatus; Bashiroh, Ainin (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The construction industry is one of the fields where the implementation of Occupational Safety and Health (K3) is still not optimal, as evidenced by the still high number of work accidents. Efforts to increase this awareness can be done early on through education and training, one of which is through Vocational High Schools (SMK). In general, students are still not aware of the possibility of work accidents. Providing K3 training from an early age can help students develop the knowledge, attitudes, and behaviors that will be needed in the workplace later. The purpose of this program is to provide knowledge and skills to students of SMKN 1 Kemlagi, Mojokerto Regency regarding the basics of construction K3. The methods used to educate students through K3 learning include lectures and socialization, as well as evaluation through pre- and post-tests. Overall, K3 education activities are able to improve the understanding of students in the Building Design Modeling and Information Department of all topics discussed, including risk control strategies, preventing and dealing with fires in the work area, recognizing personal protective equipment.